Pengaruh Ukuran Perusahaan terhadap Kinerja Keuangan Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2020-2023 - Lili Wahyuni; Witra Maison; Latifa Arrafi (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of company size on the financial performance of mining companies listed on the Indonesia Stock Exchange during the 2020–2023 period. Company size is measured using the natural logarithm of total assets, while financial performance is proxied by Return on Assets (ROA). The research method used is a quantitative approach with a simple linear regression analysis technique. Data were obtained from the company's annual financial reports published on the official website of the Indonesia Stock Exchange. The number of samples was 104 observations selected using a purposive sampling technique. Based on the results of the data analysis, it is known that company size does not have a significant effect on financial performance. This is evidenced by the t value of 0.968 which is smaller than the t table of 1.9879, and the significance value of 0.334 which is greater than 0.05. These results indicate that the size of the company does not directly determine the efficiency or profitability of the company. This finding is an important consideration for management in formulating financial and investment strategies.